The Relationship Between User Ability Response (UAR) and Intentions and Attitudes Toward Vector Control Among Users of the Geplakkin Application [Accepted] - Azizah Nur Aini; Andri Dwi Hernawan; Elly Trisnawati; Barry Caesar Octariadi (Health Dynamics, 2026)
ABSTRACTBackground: Geplakkin is a digital application that enables the general public to report, monitor, and obtain information on Aedes mosquito density as part of a monitoring system. The objective of this study was to analyze the relationship between the level of use of the Aedes mosquito app (UAR) and the intention to eliminate mosquito breeding sites, as well as the relationship between the level of use and attitudes toward eliminating mosquito breeding sites among Geplakkin app users in Pontianak. Methods: The study population consisted of households in Pontianak. A total of 240 Geplakkin app users were selected through targeted sampling. The inclusion criterion was owning a smartphone capable of installing and using the app. Data were analyzed using univariate and bivariate analyses. Bivariate analysis was performed using Pearson’s product-moment correlation and Spearman’s rank correlation. Results: The results showed a weak but statistically significant positive relationship between the level of Geplakkin app usage and the intention to eliminate mosquito breeding sites (r = 0.310, p = 0.000). The variable attitude toward mosquito breeding site elimination showed a very weak but statistically significant positive correlation with UAR (r = 0.149, p = 0.021). Both variables exhibited a positive association, indicating that higher UAR values are associated with stronger intentions and more positive attitudes toward eliminating mosquito breeding sites. Conclusion: Continued use of the Geplakkin monitoring app is recommended, as users’ positive responses to the app have the potential to strengthen their intention to eliminate mosquito breeding sites and thereby foster a positive community attitude toward mosquito breeding site elimination (PSN) efforts as part of dengue vector control.